2022
DOI: 10.3390/jmse10091271
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol Analogs in Aquatic Environments and Their Effects on Marine Species—A Review

Abstract: Bisphenol A analogs are currently used in manufacturing and as plasticizers as a substitute for bisphenol A. This replacement is taking place because bisphenol A is recognized as an endocrine disruptor chemical (EDC) that can also cause oxidative stress and genotoxic effects in aquatic species. Bisphenol A analogs have a similar chemical structure to BPA, raising doubts about their use as safer substitutes. This review intends to summarize the concentrations of BPA analogs found in aquatic environments and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 88 publications
0
3
0
Order By: Relevance
“…However, our observations of an impairment in the microalgal antioxidant system are in accordance with the bisphenols' capacity to produce ROS, which has been reported in many studies. Indeed, recently, P. tricornutum showed an increase in ROS production for most of the tested bisphenols (BPC, BPS, BPA, BPAF, BPAP, and BPFL) over 72 h at different dosages (5,20,40,80, 150 and 300 µM). In detail, BPAP showed the highest ROS production, followed by BPFL > BPAF > BPA > BPS > BPC [47].…”
Section: Biomarker Responsesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, our observations of an impairment in the microalgal antioxidant system are in accordance with the bisphenols' capacity to produce ROS, which has been reported in many studies. Indeed, recently, P. tricornutum showed an increase in ROS production for most of the tested bisphenols (BPC, BPS, BPA, BPAF, BPAP, and BPFL) over 72 h at different dosages (5,20,40,80, 150 and 300 µM). In detail, BPAP showed the highest ROS production, followed by BPFL > BPAF > BPA > BPS > BPC [47].…”
Section: Biomarker Responsesmentioning
confidence: 99%
“…Regarding the BPF, its toxic classification varies from toxic to harmful for aquatic organisms, with reported EC 50 values that range from 9.2 mg/L to 12.3 mg/L [ 18 , 19 ]. The environmental concentrations of BPA analogs are often in the range of a few ng/L [ 20 ]. However, recent studies have indicated higher concentrations, with levels of hundreds and thousands of ng/L in both fresh and marine environments [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation